Polar Bear Harvest Patterns Across the Circumpolar Arctic - Vongraven, Dag; Derocher, Andrew E.; Pilfold, Nicholas W.; Yoccoz, Nigel G. (Frontiers in Conservation Science, 2022)
Wildlife harvest remains a conservation concern for many species and assessing patterns of harvest can provide insights on sustainability and inform management. Polar bears (Ursus maritimus) are harvested over a large part of their range by local people. The species has a history of unsustainable harvest that was largely rectified by an international agreement that required science-based management. The objective of our study was to examine the temporal patterns in the number of polar bears harvested, harvest sex ratios, and harvest rates from 1970-2018. We analyzed data from 39,049 harvested polar bears (annual mean 797 bears) collected from 1970 to 2018. Harvest varied across populations and times that reflect varying management objectives, episodic events, and changes based on new population estimates. More males than females were harvested with an overall M:F sex ratio of 1.84. Harvest varied by jurisdiction with 68.0% of bears harvested in Canada, 18.0% in Greenland, 11.8% in the USA, and 2.2% in Norway. Harvest rate was often near the 4.5% target rate. Where data allowed harvest rate estimation, the target rate was exceeded in 11 of 13 populations with 1 to 5 populations per year above the target since 1978. Harvest rates at times were up to 15.9% of the estimated population size suggesting rare episodes of severe over-harvest. Harvest rate was unrelated to a proxy for ecosystem productivity (area of continental shelf within each population) but was correlated with prey diversity. In the last 5-10 years, monitored populations all had harvest rates near sustainable limits, suggesting improvements in management. Polar bear harvest management has reduced the threat it once posed to the species. However, infrequent estimates of abundance, new management objectives, and climate change have raised new concerns about the effects of harvest.